RideConnect : The Future of Auto Driver Efficiency - Gajanan Bhusare; Dinesh Bendre; Girish Bhosale; Avdhoot Walunjkar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This research paper proposes RideConnect, a mobile application designed to transform urban transportation by connecting commuters with auto-rickshaw drivers in real-time. The project addresses challenges faced by traditional taxi booking systems, including extended waiting times and suboptimal route planning, by leveraging advanced technologies such as HTML, CSS, JavaScript, React, Node.js, APIs, and databases. Key objectives include optimizing waiting times, implementing route optimization algorithms, ensuring secure payment gateways, and fostering a two-way rating system. RideConnect aims to revolutionize the rick-shaw booking experience, offering users a seamless and efficient transportation solution while creating economic opportunities for auto-rickshaw drivers.